Eagle fatalities are reduced by automated curtailment of wind turbines. Issue 3 (31st January 2021) - McClure, Christopher J. W.; Rolek, Brian W.; Dunn, Leah; McCabe, Jennifer D.; Martinson, Luke; Katzner, Todd
Abstract: Collision‐caused fatalities of animals at wind power facilities create a 'green versus green' conflict between wildlife conservation and renewable energy. These fatalities can be mitigated via informed curtailment whereby turbines are slowed or stopped when wildlife are considered at increased risk of collision. Automated monitoring systems could improve efficacy of informed curtailment, yet such technology is undertested. We test the efficacy of an automated curtailment system—a camera system that detects flying objects, classifies them and decides whether to curtail individual turbines to avoid potential collision—in reducing counts of fatalities of eagles, at Top of the World Windpower Facility (hereafter, the treatment site) in Wyoming, USA. We perform a before–after–control–impact study, comparing the number of eagle fatalities observed at the treatment site with those at a nearby (15 km) control site without automated curtailment, both before and after the implementation of automated curtailment at the treatment site. After correcting for carcass detection probability and scaling fatality estimates to turbine‐years, we estimate that the number of fatalities at the treatment site declined by 63% (95% CI = 59%–66%) between before and after periods while increasing at the control site by 113% (51%–218%). In total, there was an 82% (75%–89%) reduction in the fatality rate at the treatment site relative to the control site. Synthesis and applications . Automated curtailment of wind turbine operation substantially reduced eagle fatalities. This technology therefore has the potential to lessen the conflict between wind energy and raptor conservation. Although automated curtailment reduced fatalities, they were not fully eliminated. Therefore, automated curtailment, as implemented here, is not a panacea and its efficacy could be improved if considered in conjunction with other mitigation actions. Abstract : Automated curtailment of wind turbine operation substantially reduced eagle fatalities. This technology therefore has the potential to lessen the conflict between wind energy and raptor conservation. Although automated curtailment reduced fatalities, they were not fully eliminated. Therefore, automated curtailment, as implemented here, is not a panacea and its efficacy could be improved if considered in conjunction with other mitigation actions.